Requirements for the stone fruit certification programme in Spain - Pallás, Vicente; Badenes, María L.; Llácer, Gerardo (CIHEAM, 2023)
In 1977, an agreement between the Institute National de Investigaciones Agrarias (INIA) and The Institute National de Semillas y Plantas de Vivero (INSPV) was signed for the expressed purpose of selection, reproduction and control of fruit materials by the fruit department of the Research Center of the INIA in Zaragoza (Cassallo et al., 1988). On 16th July, 1982, the Technical regulations for the Control and Certification of Nursery Plants were approved. These regulations were modified and recently updated with the Real Decreto 929/1995, dated 9 June.